2020
DOI: 10.1142/s0217751x20400552
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational interaction in astrophysics in Riemann-Cartan space-time and vacuum torsion

Abstract: The role of space-time torsion in astrophysics in the frame of minimum gauge gravitational theory in Riemann-Cartan space-time is discussed. The influence of the vacuum torsion on dynamics of astrophysical objects induced by the interaction of their spin momenta with vacuum torsion is studied. Possible manifestations of such interaction are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Consequently, the dynamics of metric-affine gravity with torsion is discussed in [76]. However, there are reports about the metric of the axially symmetric solution [77,78] in empty space and its application to the rotation curves of spiral galaxies [77]. It was found that the vacuum torsion interacts with spin momenta of astrophysical objects which can lead to modifications of Newton's law [78].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the dynamics of metric-affine gravity with torsion is discussed in [76]. However, there are reports about the metric of the axially symmetric solution [77,78] in empty space and its application to the rotation curves of spiral galaxies [77]. It was found that the vacuum torsion interacts with spin momenta of astrophysical objects which can lead to modifications of Newton's law [78].…”
Section: Introductionmentioning
confidence: 99%
“…The transition to the Friedman mode occurs when the value ε becomes much less than εmax and the value X is approaching 1; then according to (20) H ∼ √ ε, approximately such a transition occurs when ε = ε4 ∼ 0.001 εmax . By using the equation of energy conservation in dimensional form (see (13)) we obtain the dependence ε = ε( x0 ) at extreme conditions presented in figure 3. Assuming that limiting energy density corresponds to x0 = 0, we find an estimate for the moments of time x0 1 = ±0.718, x0 2 = ±1.056, x0 3 = ±1.768, x0 4 = ±31.344 corresponding to ε1 , ε2 , ε3 .…”
Section: Jcap03(2022)027mentioning
confidence: 99%
“…Significant changes in the gravitational interaction in the case of astrophysical objects with energy densities small compared to the limiting energy density take place when their rotational moments interacting with torsion are taken into account. Thus, the interaction of vacuum torsion with the rotational moments of astrophysical objects (stars, galaxies) studied in the frame of minimum GTRC [12] leads to the appearance, in addition to the Newtonian gravitational attraction force, of an additional force caused by their interaction [11,13,14].The magnitude of this force, as well as in general the physical consequences associated with the interaction of torsion with the rotational moments of astrophysical objects, depend on the restrictions imposed on the parameters b and α. Taking into account the value of the cosmological constant, following from observations, we obtain a restriction on the parameters b and α while the condition 0 < 1 − b f 0 1 takes place.…”
Section: Jcap03(2022)027mentioning
confidence: 99%